Entrepreneurial intention among Bumiputera students / Siti Natrah Dolwadi - Dolwadi, Siti Natrah (2014)
This study is conducted as a partial fulfillment of the coursework of Industrial Training Project Paper (MKT 669). This title of study is entrepreneurial intention among students. Many universities in Malaysia have introduced entrepreneurship education to promote the interest of students to becoming entrepreneurial behavior in the future. The researcher seeks the undergraduates’ perceptions on factors that influence them to entrepreneurial intentions. This study focused in three elements of entrepreneurial intention that is attitude toward the behavior, subjective norms and perceived behavioral control. All this elements used as an independent variable and the dependent variables is entrepreneurial intention. The main objectives of this study are to understand how attitude toward the behavior, subjective norms and perceived behavioral control affect entrepreneurial intention among students. Through this study, it will help Officer Youth and Sport to identify the new strategy about the entrepreneur that can be used in increase their programs amongst youth. The primary data of this study was gathered by distributing 100 survey questionnaires to respondents at UiTM Kampus Bandaraya Melaka. The questionnaires are divided into six sections which consist of section A until section F. All the data was analyzed using the Statistical Package for Social Science (SPSS) version 19.0. The Cronbach’s Alpha Reliability test which can ensure the high reliability result that was conducted on every variable. In this research, the researcher used the Pearson Correlation Coefficient and Multiple Linear Regression Analysis that were conducted to observe independent variables. All the variables have significant relationship with entrepreneurial intention. Besides that, the researcher also used Independent Sample T-test to test on personal details of respondents. In the end of the study, the findings, recommendation and conclusion for the future research were discussed.